Enhancing French Reading Comprehension by Implementing a Project Based-Learning - Rosita, Diana; Rini, Setia; Trisna, Indah Nevira; Zuleika, Tika (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to determine and describe the comparison before and after the implementation of Project-Based Learning (PjBL) on the French reading comprehension abilities of students in the French Education Study Program, measured by reading level indicators equivalent to the B2 level in the CEFR. The method used is quantitative, with a quasi-experimental research design. The population consisted of all students in this study program, totaling 186 students in the odd semester of the 2023/2024 Academic Year. The sample was selected through purposive sampling, comprising 20 students at the B2 level. The highest score obtained during the pretest was 77.5, while the highest posttest score was 75. The average student score during the pretest was 54, but it dropped to 50 in the posttest. The t-test results showed a 2-tailed significance value of more than 0.05, indicating no significant influence on the ability to understand French text after implementing PjBL. Based on the questionnaire, students reported increased motivation to read French texts, better understanding of sentences, and improved ability to find the main idea. They also noted enhancements in teamwork, creativity, and critical thinking, although they still required guidance from lecturers. Despite the positive reception and impact of the PjBL model on learning, there was no significant effect on students' French reading comprehension abilities after its implementation. Further research should investigate the factors that influence students' reading comprehension results.